Reforming of Ethanol to Produce Hydrogen over PtRuMg/ZrO2 Catalyst - Josh Y. Z. Chiou; Chi-Han Wang; Shih-Yi Yang; Jia-Lin Bi; Chia-Chieh Shen; Chen-Bin Wang (Journal of Nanotechnology)
A modified PtRu/ZrO2 catalyst with Mg is evaluated for the oxidative steam reforming of ethanol (OSRE) and the steam reforming of ethanol (SRE). In order to understand the variation in the reaction mechanism on OSRE and SRE, further analysis of both fresh and used catalyst is concentrated on for TEM, TG, Raman, and TPR characterization. The results show that the OSRE reaction requires a higher temperature (𝑇𝑅∼390°C) to achieve 100% ethanol conversion than the SRE reaction (𝑇𝑅∼2500°C). The distribution of CO is minor for both reactions (< 5% for OSRE, < 1% for SRE). This demonstrates that the water gas shift (WGS) reaction is an important side-reaction in the reforming of ethanol to produce H2 and CO2. A comparison of the temperature of WGS (𝑇WGS) shows it is lower for the SRE reaction (𝑇WGS∼250°C for SRE, ~340°C for OSRE).